Sex and Age Morphometric Variations in Bony Nasolacrimal Duct and Fossa for Lacrimal Gland in Mexican Population - Aguilar Morales, Kouatzin; Avalos Fernández, Cesia G.; Morales Avalos, Rodolfo; Mohamed Noriega, Karim; Sánchez Mejorada, Gabriela; Martínez Fernández, David. A.; Mohamed Noriega, Jibran; Lugo Guillen, Roberto A.; Villanueva Olivo, Arnulfo; Cuervo Lozano, Edgar. E.; Mohamed Hamsho, Jesús; Elizondo Omaña, Rodrigo Enrique; et al. (Sociedad Chilena de Anatomía, 2018)
SUMMARY: Primary acquired nasolacrimal duct obstruction is greater in women over 40 years and has been associated with morphometric variations in the osseous nasolacrimal duct, which varies according to age and sex. The objective is to determine variations regarding sex and age of the nasolacrimal duct and osseous fossa for lacrimal gland. One hundred sixteen dry orbits from Mexican population were analyzed; subdivided into four groups based on age and sex. The length, transverse and anteroposterior diameters of the bone entrance of the nasolacrimal duct, and the length and width of the fossa for lacrimal gland were determined. Statistical tests were applied to determine the significance of the differences found between groups. The nasolacrimal duct in women had shorter length than men in both age groups. The entrance had a wider transverse diameter in women than men independently of age and its anteroposterior diameter was shorter in men under 40 years than over 40 years. The fossa for lacrimal gland was larger in women under 40 years than in men of same age group and women over 40 years old. The lower third of the was wider in women under 40 years than in women over 40 years. Our study confirms significant differences between sex and age groups in some of the morphometric measurements of bony nasolacrimal duct and fossa for lacrimal gland in Mexican population. Comparative studies with and without clinical illness are needed to clarify if the bony characteristics of those structures participate in the etiopathogenesis and distribution differences observed in sex, age and ethnicity of thisillness. KEY WORDS: Nasolacrimal duct; Fossa for lacrimal gland; Morphometry; Primary acquired nasolacrimal duct obstruction